THE MANAGEMENT TOOLS USED IN THE DECISION-MAKING PROCESS - Daniela POPESCU; Sorina GÎRBOVEANU (Management & Marketing)
The specificity of the different management tools and their diversification have represented the starting point for taking into consideration the process decision program chart and the activity network diagram. The analysis of these management tools gives the possibility of understanding the complexity of the management problems and their practical importance. At the same time, going in the intimacy of these instruments shows us the complex relations among components, activities, management matrices. That is why we resorted to the separate discussion of these tools in order to point out both the specific elements of these tools and the ways of putting these into practice.